Identification and characterization of a promiscuous metallohydrolase in metallo-β-lactamase superfamily from a locally isolated organophosphate-degrading Bacillus sp. strain S3wahi - Azman, Ameera Aisyah; Muhd Noor, Noor Dina; Leow, Adam Thean Chor; Mohd Noor, Siti Aminah; Mohamad Ali, Mohd Shukuri (Elsevier B.V., 2024)
In this present study, characteristics and structure-function relationship of an organophosphate-degrading enzyme from Bacillus sp. S3wahi were described. S3wahi metallohydrolase, designated as S3wahi-MH (probable metallohydrolase YqjP), featured the conserved αβ/βα metallo-β-lactamase-fold (MBL-fold) domain and a zinc bimetal at its catalytic site. The metal binding site of S3wahi-MH also preserves the H-X-H-X-D-H motif, consisting of specific amino acids at Zn1 (Asp69, His70, Asp182, and His230) and Zn2 (His65, His67, and His137). The multifunctionality of S3wahi-MH was demonstrated through a steady-state kinetic study, revealing its highest binding affinity (KM) and catalytic efficiency (kcat/KM) for OP compound, paraoxon, with values of 8.09 × 10−6 M and 4.94 × 105 M−1 s−1, respectively. Using OP compound, paraoxon, as S3wahi-MH native substrate, S3wahi-MH exhibited remarkable stability over a broad temperature range, 20 °C – 60 °C and a broad pH tolerance, pH 6–10. Corresponded to S3wahi-MH thermal stability characterization, the estimated melting temperature (Tm) was found to be 72.12 °C. S3wahi-MH was also characterized with optimum catalytic activity at 30 °C and pH 8. Additionally, the activity of purified S3wahi-MH was greatly enhanced in the presence of 1 mM and 5 mM of manganese (Mn2+), showing relative activities of 1323.68 % and 2073.68 %, respectively. The activity of S3wahi-MH was also enhanced in the presence of DMSO and DMF, showing relative activities of 270.37 % and 307.41 %, respectively. The purified S3wahi-MH retained >60 % residual activity after exposure to non-ionic Tween series surfactants. Nevertheless, the catalytic activity of S3wahi-MH was severely impacted by the treatment of SDS, even at low concentrations. Considering its enzymatic properties and promiscuity, S3wahi-MH emerges as a promising candidate as a bioremediation tool in wide industrial applications, including agriculture industry.